Ujub Sesaji as a Vehicle of Character Education: A Thomas Lickona Perspective on Javanese Buddhist Puja Bakti in Boyolali Regency - Niken Wardani; Budi Utomo (AL-ISHLAH: Jurnal Pendidikan, 2026)
Character education embedded in indigenous religious ritual remains underexplored, particularly within syncretic Javanese Buddhist communities. This study examines the pedagogical function of the Ujub Sesaji ritual in Javanese-language Puja Bakti among Buddhist communities in Boyolali Regency, Indonesia, using Thomas Lickona’s tripartite framework of moral knowing, moral feeling, and moral action. The study involved five purposively selected informants drawn from three vihara congregations in Boyolali Regency: a regency-level Buddhist religious extension officer, a senior religious figure (sesepuh), a temple chairperson, a women’s community leader, and a youth representative, all of whom hold active roles in sustaining Javanese-language Puja Bakti within their congregations. Employing a qualitative descriptive-hermeneutic design, the study observed the sequence and verbal content of Ujub Sesaji during Puja Bakti services and analyzed semi-structured interview data together with ritual texts, verbal formulas, and the symbolic meaning of ritual offerings. The findings suggest that Ujub Sesaji functions as a non-formal moral learning practice: symbolic offerings cultivate moral cognition; Javanese recitation and communal participation intensify gratitude, reverence, compassion, and humility; and repeated ritual practice habituates sincerity, cooperation, discipline, and intergenerational responsibility. The study extends the discussion of character education beyond formal schooling by showing how local religious-cultural rituals can support community-based moral formation.